Gold-Labeled Bovine Fibrinogen for Study of Human Platelets - Grouse, Lynette H; White, James G (Thrombosis and Haemostasis, 1989)
Fibrinogen coupled to colloidal gold has proven to be a useful agent for probing the glycoprotein IIb-IIIa receptor on human and bovine platelets at the ultrastructural level. The reagent has helped to demonstrate fundamental differences in the reorganization of the fibrinogen receptors on human and cattle platelets following surface activation. However, commercial preparations of human fibrinogen have not yielded a stable reagent in our hands when coupled to colloidal gold. The present study has substituted bovine for human fibrinogen. Bovine fibrinogen gold proved to be a more stable reagent and could be substituted for human fibrinogen gold in all experiments on human and bovine platelets.
Keywords: GPIIb-IIIa; Fibrinogen binding; Electron microscopy; Gold labeling